Report of five novel and one recurrentCOL2A1 mutations with analysis of genotype-phenotype correlation in patients with a lethal type II collagen disorder. Issue 4 (1st April 2000) - Mortier, Geert R; Weis, MaryAnn; Nuytinck, Lieve; King, Lily M; Wilkin, Douglas J; De Paepe, Anne; Lachman, Ralph S; Rimoin, David L; Eyre, David R; Cohn, Daniel H
Abstract : Achondrogenesis II-hypochondrogenesis and severe spondyloepiphyseal dysplasia congenita (SEDC) are lethal forms of dwarfism caused by dominant mutations in the type II collagen gene ( COL2A1 ). To identify the underlying defect in seven cases with this group of conditions, we used the combined strategy of cartilage protein analysis and COL2A1 mutation analysis. Overmodified type II collagen and the presence of type I collagen was found in the cartilage matrix of all seven cases. Five patients were heterozygous for a nucleotide change that predicted a glycine substitution in the triple helical domain (G313S, G517V, G571A, G910C, G943S). In all five cases, analysis of cartilage type II collagen suggested incorporation of the abnormal α1(II) chain in the extracellular collagen trimers. The G943S mutation has been reported previously in another unrelated patient with a strikingly similar phenotype, illustrating the possible specific effect of the mutation. The radiographically less severely affected patient was heterozygous for a 4 bp deletion in the splice donor site of intron 35, likely to result in aberrant splicing. One case was shown to be heterozygous for a single nucleotide change predicted to result in a T1191N substitution in the carboxy-propeptide of the proα1(II) collagen chain. Study of the clinical, radiographic, and morphological features of the seven cases supports evidence for a phenotypic continuum between achondrogenesis II-hypochondrogenesis and lethal SEDC and suggests a relationship between the amount of type I collagen in the cartilage and the severity of the phenotype.